Entre o produzir e o reproduzir na agricultura familiar fumageira de Arroio do Tigre/RS - Redin, Ezequiel (2011)
This work treats of the analysis of the agriculture family fumageira in the municipal district of Arroio do Tigre/RS, taking potentially as starting point the strategies of reproduction of short cycle that it involves the primary section, mover of the local economy. The objective of this study was to understand and to explain the factors that influence the family farmers to choose for the production family fumageira as strategy of main reproduction, through the notes and appreciations of the analysis of secondary data and of the speech that you/they orientate the rural producers in the mark of his/her development, mainly economical. For his/her accomplishment we used the bibliographical research so much and of secondary sources, as of observations and interviews in field research. With base in the bibliography about the strategies, the socket of decision and the production forms, relationship and commercialization of the culture of the tobacco; described and to analyze the transformations in the rural space, the continuity of the activities and the difficulties of the agricultural section; looking at aspects of the relationship interns and external, of the integration system, of the farmer due to the variations of the market and their production forms and reproduction in the rural, conditions these that explain, partly, the reason for which the agriculture of family base of Arroio do Tigre sustains 2.610 families producing of tobacco reaching 90% of the rural producers. In the field research, we stimulated ourselves to unmask the reasons for which the culture of the tobacco answers for 43,8 million Real in the municipal district, as well as it represents 57% of the value produced in the property, according to data of Afubra. We also verified that the fumicultura is the car-boss of the farmers' agricultural and economical activity, however, thick way, most of the properties presents production for the self-consumption, marketing the surplus. Among the results that deserve prominence: a) we marked three types of strategies: strategy of main reproduction (I smoke); strategy of complementally reproduction (corn, wheat, bean and soy and cut livestock and milk); and strategy of basic reproduction (self-consumption); b) we identified three types of tobacco farmers: with high productive restriction, with relative restriction and low restriction; c) in relation to the important economical factors for the production of tobacco are: high gross income for hectare; financing and credit of inputs and facilities; technical support; he/she guaranteed of purchase of the harvest; I hold agricultural; intensive production system; negotiation of prices before, in the moment and powders commercialization; use of hand of family work; rusticity of the culture; possibility of two cultures and responsibility of the logistics of the product for the company. The elements no economical they are: to know to do; recognition; trust; productive tradition; safety and cooperation action between agribusinesses and fumicultor. Finally, one of the most interesting results went to notice that the families, thick way, they are not devoted the culture of the tobacco exclusively, tends in his/her property a fan of self-consumption products and some cultures returned to the market as support strategy the family farmers' reproduction in the rural space.